Antecedents of salesperson performance in information service industry: The role of guanxi, adaptive selling behaviors and customer orientation - Thi-Thuy-Linh Nguyen; Xuan-Quynh Hoang; Pham Thi Lien; Thanh-Hang Pham; Hiep-Hung Pham (Cogent Business & Management, 2022)
This research aims to investigate the determinants of salesperson performance with a focus on the role of customer-centric selling behaviors in the interaction with Guanxi-a measure of the quality of customer-salesperson relationship. The study examines two well-established constructs in the body of sales literature, namely customer orientation and Adaptive selling behavior to shed light on the inconclusive relationship between these antecedents and sales performance in prior works. Using a sample of 204 salespeople in the Information service industry, the authors tested several hypotheses employing the structural equation model (SEM). The results suggest that the adoption of adaptive selling and Customer-oriented behaviors may help salespeople improve performance. Moreover, Guanxi does play some role in explaining sales performance of B2B salespeople. Based on the findings, theoretical contributions and managerial implications, as well as suggestions for future research, will also be presented. In the business-to-business (B2B) context, salespeople are the critical link between a company and its customers; therefore, understanding their performance is a key concern of sales managers as well as researchers in the discipline. However, due to the complex nature of selling activities, the extant literature has not agreed upon the universal factors that may ensure salespeople's success. The research also takes into account the China-originated construct called Guanxi, which is expected to reflect the quality of the relationship between salesperson and customer. Few prior studies have grouped guanxi with selling behaviors in an explanatory model of sales performance. Therefore, studying this interaction may provide more insights into how to improve the performance of the salesforce.
Keywords: 650; adaptive selling behaviors; business-to-business sales performance; customer orientation; guanxi; information service industry